2022
DOI: 10.1158/1538-7445.panca22-b065
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B065: Polymerase theta inhibition activates the cGAS-STING signaling pathway and elicits an immune response in homologous recombination-deficient pancreatic adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy that harbors mutations in homologous recombination (HR) repair genes in up to 25% of cases. Defects in HR impart to tumor cells a specific vulnerability to poly-ADP ribose polymerase inhibitors and platinum-based chemotherapy. However, not all patients respond, and some who initially respond develop resistance and progress. Thus, new therapies that are effective against HR-deficient PDAC are needed. Here, we show that inactivation of the HR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…BRCA2 deficiency induces a high frequency of stalled DNA replication forks that enhance the number of cGAS-positive micronuclei, consequently provoking a cascade of inflammatory cytokine expression [103]. Similar results have been found in DNA polymerase θ (POLQ) knockdown BRCA2-deficient pancreatic ductal adenocarcinoma cells [104]. However, the latest solid research has indicated that the chromatin bridges serve as the direct and strong stimulators of cGAS rather than micronuclei [105].…”
Section: The Regulation Of Innate Immune Sensors By Ddr Componentsmentioning
confidence: 55%
“…BRCA2 deficiency induces a high frequency of stalled DNA replication forks that enhance the number of cGAS-positive micronuclei, consequently provoking a cascade of inflammatory cytokine expression [103]. Similar results have been found in DNA polymerase θ (POLQ) knockdown BRCA2-deficient pancreatic ductal adenocarcinoma cells [104]. However, the latest solid research has indicated that the chromatin bridges serve as the direct and strong stimulators of cGAS rather than micronuclei [105].…”
Section: The Regulation Of Innate Immune Sensors By Ddr Componentsmentioning
confidence: 55%
“…These two recent studies demonstrate that, in certain HR-deficient settings, Pol θ inhibition has a substantial impact on immune activation through stimulation of the cGAS/STING pathway (14,16). HR-deficient PDAC models, relative to PDAC models that lacked HR-associated gene mutations.…”
Section: Unresolved Questions and Translational Implicationsmentioning
confidence: 99%
“…In the current issue of the JCI, Oh and Wang, et al report findings that reveal the impact of Pol θ inhibition on immune activation (Figure 1) (14). Their study focuses on pancreatic ductal adenocarcinoma (PDAC), motivated by the observations that nearly a quarter of PDAC cases are associated with HR-associated gene alterations and that POLQ overexpression correlates with worse prognosis in two independent cohorts of PDAC patients.…”
Section: Pol θ Inhibition Activates the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations